“I SHOULD LOVE LOCAL PRODUCT” : LOCAL PRODUCT LOYALTY WITHIN UTILITARIAN PERSPECTIVE - Ignasius Heri Satrya Wangsa; Maria Josephine Tyra (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2022)
Social aspect in consumer behavior has placed the essence of interaction between consumer and his environment. It is within the interactive process that consumer begins to recognize his role. Therefore, there are two domains in the context of local product loyalty. First, pressure of social function directs the consumption to satisfy certain level of social consequences ie. the deployment of loyalty as part of patriotism “I should love local product”. Second, economic rationality is always trying to seek the best combination in which resources can be allocated efficiently. In the first domain the discussion is mainly about local product consumption ie. nationalism-based consumption, while in the second one the utilitarian perspective is introduced as complement in the discourse of the rationales behind local product consumption. Participants in this research were selected and their narratives of local product consumption were analyzed through mixed-method approach. Marketing implication was also discussed to contribute in the theory of local product consumption within utilitarian perspective.